Evaluating tumour after care in oral squamous cell carcinoma: Insights into patients' health related quality of life. Issue 2 (February 2017) - Bissinger, Oliver; Rau, Andrea; Koerdt, Steffen; Wolff, Klaus-Dietrich; Kesting, Marco Rainer; Götz, Carolin
Abstract: Introduction: Tumour aftercare (tac) is an essential tool in oncology. The main aim of these follow ups is to diagnose recurrence and second tumours from the beginning. Tac appointments can create a special environment for patients' further concerns. The purpose of the current study was to evaluate tac of patients diagnosed with OSCC and to investigate their health related quality of life (hrql). Material and methods: A German questionnaire was created by two maxillo-facial surgeons with several years of tac experience. It was handed out to 100 German-speaking OSCC patients during tac. Results were statistically evaluated with SPSS (SPSS version 21.0; SPSS, IBM; Chicago, IL, USA). The inclusion criterion was that diagnosis and surgery were performed at our department and that the patients attended our tac regularly. Results: Side effects such as difficulties in speaking and swallowing were evaluated as being significantly higher in cases who were administered adjuvant radiochemotherapy (art) compared with the surgical therapy group (stg) (p = 0.03). Anxiety occurred in 80% of all female patients (p = 0.02), 90% of them with a high psychological strain because of the cancer diagnosis (p = 0.04). Discussion: To date, tac is a rare topic in literature. Moreover, only a few trials have focused on hrql in OSCC. A main result of the current study is that during tac, OSCC patients should be regularly questioned about their symptoms and mental state. Further, the need of the majority of OSCC patients for coping therapies can concomitantly be evaluated. Conclusion: The evaluation of tac is of high relevance. The results of the current study have encouraged us to establish this questionnaire as a routine tool in our tac.